Pedicle Involvement on MR Imaging Is Common in Osteoporotic Compression Fractures - Ishiyama, M. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Pedicle involvement on MR imaging has been considered specific for malignancy. However, we also noted the findings in many patients with osteoporosis and hypothesized that it is not specific for malignant lesions. The aim of this study was to evaluate the prevalence of pedicle involvement in painful osteoporotic compression fractures and to determine whether the sign is specific for malignancy. MATERIALS AND METHODS: We retrospectively reviewed MR images and CT scans of 152 patients who underwent PV for painful compression fractures. There were 140 patients (225 vertebrae) with osteoporotic fractures and 12 patients (19 vertebrae) with malignant fractures. Three radiologists evaluated the degree and extent of signal-intensity changes of the pedicle on MR imaging by consensus. The CT findings were also evaluated. The χ(2) test was used for statistical analyses. RESULTS: Of the 225 vertebrae of osteoporotic fractures and 19 vertebrae of malignant fractures, pedicle involvement on MR imaging was seen in 144 (64%) and 16 (84.2%) vertebrae, respectively, and there was no statistically significant difference (P = .065). Positive pedicle involvement in osteoporotic fractures was seen in 84 (77%) of 109 vertebrae with early-phase fractures (≤3 months) and 60 (51.7%) of 116 vertebrae with chronic-phase fractures (>3 months), and this was statistically significant (P < .001). Among 144 osteoporotic vertebrae that showed positive pedicle involvement on MR imaging, 45 (31%) showed pedicle fractures and 55 (38.2%) showed sclerotic change on CT. CONCLUSIONS: Pedicle involvement was seen frequently in patients with osteoporotic compression fractures and was not specific for malignancy in our study group.